PENGARUH KELOMPOK NEOKONSERVATISME TERHADAP KEBIJAKAN LUAR NEGERI INVASI AFGHANISTAN OLEH AMERIKA SERIKAT (2001) - Maharani, Dina Cassa; Ratimanjari, Kinanti; Kolit, Markus Yulandris Abram; Ramadhani, Tessa Olivia (Global and Policy Journal of International Relations, 2017)
ABSTRACTThe United States used the military in response to the attacks on September 11, 2001. The shape of the response was the US invasion of Afghanistan in 2001. Moreover, the use of explorations of the coalition decision-unit type was able to explain the role from the group to the decision-making process. According to the analysis of the coalition decision-unit type, the decision-making process within the United States government contains the interaction of two major groups in the politics of the United States government itself. The two major groups are the Republican Neoconservatism and New Left Democrats. In the current decision-making process, the seat of the United States government was dominated by the majority of the Neoconservatism group. The dominance of the Neoconservatism group made interaction and debate in the US foreign policy making process at the time was not so explicit. It also ultimately resulted in a dominant foreign policy.Keywords: Invasion, Foreign Policy, Neoconservatism, Dominant, Coalition Decision-UnitDOI: https://doi.org/10.33005/jgp.v5i01.1898